Embrioni soprannumerari, ricerca scientifica e divieti normativi. Riflessione a margine delle prime pronunce della giurisprudenza italiana e della Corte EDU (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
Article 13 L.40 / 04 provides for the total ban of clinical and experimental human embryo research. This principle operates independently of any assessment of the current condition in which the embryo is primary with regard to (non) possibilities relative (supernumerary embryos or abandoned) or absolute (non-viable embryos or those with chromosomal / genetic disorders) to be used for playback. The provision is, icto oculi, unreasonable and disproportionate because it does not allow to operate the necessary balance with the constitutionally protected interests related to the self-determination of the couple and scientific research aimed at the protection of individual and collective health. Some national judges and the Court of Human Rights rulings meeting for the first time the issue has by now acquired growing importance and topical relevance in view of the importance assumed in the therapeutic area of clinical research through the use of embryonic stem cells.
Keywords: Embryo research; Health; Assisted reproduction; Balancing of Interests.